Isolation of peat soil bacteria producing antimicrobial agents against Escherichia coli and Salmonella Typhimurium - Mahdiyah, Dede; Sari Darsono, Putri Vidia; Hidayah, Nur; Mukti, Bayu Hari (Science, Engineering and Health Studies, 2025)
The global rise of antimicrobial resistance poses a severe threat to public health, demanding the discovery of novel antibacterial agents. Peat soil is an extreme environment that can be used to isolate bacteria that produce bioactive compounds. This study examined the antibacterial activity of peat soil bacteria against Escherichia coli and Salmonella Typhimurium. Peat soil bacteria were isolated using tryptone soy agar (TSA), and their morphology and characteristics were assessed (Gram staining, catalase activity). The antibacterial activity of these bacteria was examined using the well diffusion method. The minimum inhibitory concentration (MIC) of each isolated substance was determined using the dilution method, and the minimum bactericidal concentration was determined by the spread plate method. Nine bacterial isolates, termed peat soil bacteria-1–9 (PSB1–9), were obtained at dilutions of 1 × 10−7–1 × 10−1 on TSA. Of these, PSB-7, PSB-8, and PSB-9 exhibited potential antibacterial activity against S. Typhimurium and E. coli. These isolates were characterized as Gram-positive rods. The MICs of PSB-7–9 against E. coli were 4, 3, and 3 mg/mL, respectively. For S. Typhimurium, the MICs were 3, 4, and 4 mg/mL, respectively. However, none of the isolates exhibited bactericidal activity against either pathogen.